Setan, syaitan, sultan - Hussien Alattas, Syed. (Subang Jaya, Selangor Darul Ehsan : Sun & Son Sdn. Bhd., 2012)
On personality and behavior among the Malaysian leaders.
In Malay, and two articles in English.
Keywords: Politicians -- Malaysia -- Conduct of life; Malays (Asian people) -- political activity -- Malaysia